2014
DOI: 10.1152/ajpregu.00160.2014
|View full text |Cite
|
Sign up to set email alerts
|

Influence of serotonergic mechanisms on the urine flow rate in male rats

Abstract: This study extensively examined the role of a 5-HT 1A receptor in controlling voiding function in anesthetized male rats. A simultaneous recording of the intravesical pressure (IVP), external urethral sphincter (EUS)-electromyography (EMG), and urine flow rate (UFR) during continuous cystometry was used. 8-Hydroxy-2-(di-n-propylamino)-tetralin (8-OH-DPAT), a 5-HT 1A receptor agonist, significantly improved the voiding efficiency, as detected by increases in the evoked contraction amplitude, EUS burst period, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…The surgical procedure for the recordings was performed as previously reported [12,14]. The femoral vein was catheterized for fluid infusion, and the body temperature was maintained at 36-38°C by using a recirculating water blanket.…”
Section: Simultaneous Recording Of Ivp Eus-emg and Ufrmentioning
confidence: 99%
“…The surgical procedure for the recordings was performed as previously reported [12,14]. The femoral vein was catheterized for fluid infusion, and the body temperature was maintained at 36-38°C by using a recirculating water blanket.…”
Section: Simultaneous Recording Of Ivp Eus-emg and Ufrmentioning
confidence: 99%
“…In the absence of direct measurements of voiding flow, an estimate of mean VFR can be obtained using several methods (8), including dividing VV by the duration of voiding represented by either: 1) bladder CD, 2) the TSP of the EUS EMG, or 3) the period of EUS bursting (BD). Recent experiments by Fan et al (9) in which urethral flow was directly monitored with a flow meter attached to the urethra in anesthetized male Sprague-Dawley rats revealed that voiding occurs during the period of EUS bursting. Thus VFR in the present experiments was estimated by dividing the VV by duration of voiding measured indirectly by duration of EUS bursting (BD).…”
Section: Methodsmentioning
confidence: 99%
“…Our recent study indicated that the 5-HT 1A agonist 8-OH-DPAT significantly reduced the UFR during voiding in male rats (13). Furthermore, recent studies have demonstrated that 8-OH-DPAT increases urethral pressure (resistance) during the voiding reflex in male rats; however, it significantly reduces the pressure in female rats (14).…”
mentioning
confidence: 89%
“…An ultrasonic flow probe (ME2PXN, Transonic Systems, Ithaca, NY) connected to a flowmeter (TS410, Transonic Systems) was used for UFR measurements. The flow probe was placed around the most distal part of the urethra (13,29,33).…”
Section: General Preparationsmentioning
confidence: 99%
See 1 more Smart Citation